Modelling of the rationally deployment of observing systems - Nasibov, Yashar Ali оgly; Bayramov, Azad Agalar oğlu; Sabziev, Elhan Nariman oglu; Hashimov, Elshan Giyas oğlu (Національний технічний університет "Харківський політехнічний інститут", 2019)
The various types of electron-optical supervisory control systems (SCS) have been used in Armed Forces of many advanced countries. The mission of these SCS is to supervise day and night enemy troops, technics and weapon systems, frontier intruders with high precision a great and middle distance. The SCS optimal deployment in mountainous terrain makes possibility to use rationally SCS number, because SCS has very much costs. Using the rationally SCS number we can reduce a necessity of the specialist number. Also, it accelerates comander’s correct decision making. The optimal deployment of SCS on a terrain is one of important task of military reconnaissance. The specific character of such task is that the necessary for continuing surveillance and control military objects can be located in specific zones of terrain (for examples, in canyons, along of river etc.). Accessible places of SCS set are situated on some distance from these zones. The number of SCS is limited; therefore, it is impossible to distribute theirs on the all set points. It is necessary to select such SCS set points that the zone observation range would be the largest. In present paper the mathematical model of the rationally deployment of technical observing systems in mountainous terrain has been developed and offered. The determination method of visibility level between selected terrain points has been developed. The assesment criterion of rationally deployment and the algorithm of fast solution have been offered.

У збройних силах багатьох розвинених країн використовуються різні види електронно-оптичних наглядових систем (SCS). Призначення цих SCS полягає в цілодобовому точному контролі на близькому і далеких відстанях за військами супротивника, його технікою і озброєнням, а також за порушниками кордонів. Оптимальне розташування SCS в гористій місцевості сприяє можливості використовувати раціональну кількість SCS, тому що вартість SCS є дуже високою. Використовуючи раціональну кількість SCS можливо скоротити кількість необхідних фахівців. Це також скорочує час прийняття рішення командуванням. Оптимальне розташування SCS на місцевості є одним з важливих завдань військової розвідки. Специфічний характер цього завдання полягає в необхідності тривалого спостереження за військовими об'єктами, які можуть бути розташовані в особливих зонах на місцевості (наприклад, в каньйонах, уздовж русла річок тощо). Місця розташування SCS можуть розташовуватися на різних відстанях від цих зон. Кількість SCS обмежена, тому неможливо встановити їх на всіх обраних точках. Необхідно вибрати такі місця розташування SCS, щоб зона огляду була б максимальною. У даній статті пропонується розроблена авторами математична модель раціонального розташування технічних систем спостереження в гористій місцевості. Розроблено метод визначення рівня видимості між обраними точками на місцевості. Запропоновані критерії оцінки раціонального розміщення і алгоритм швидкого вирішення цього завдання.
Моделювання раціонального розташування систем спостереження
Keywords: mountainous terrain; mathematical model; гориста місцевість; математична модель